The Effect of Task-Based Language Teaching on Students Speaking Achievement at the First Grade of SMAN 1 Bandar Lampung - Kory Dita Iswari; Mahpul Mahpul; Gede Eka Putrawan (Aksara: Jurnal Bahasa dan Sastra, 2017)
The aim of this study was to find out the constraints of teaching speaking using TBLT on students speaking achievement at the first grade students of SMAN 1 Bandar Lampung. This was a qualitative research. The subjects were 29 students of the first grade of SMAN 1 Bandar Lampung. Observation and interview were used as the research instruments. The result of the research showed that the contraints of teaching speaking using TBLT were the role of teacher in giving instructions, the role of task itself, and students background knowledge especially on language forms and vocabularies. This suggests that speaking through TBLT helps students express their ideas and makes them more active in the class. DOI: http://dx.doi.org/10.23960/aksara/v18i2.pp113-121